"I think it's a bit early for now": impact of psychological factors on drafting advance directives among cancer patients. Issue 1 (2nd January 2019) - Cannone, Patrice; Tomasini, Pascale; Paul, Merlin; Barlesi, Fabrice; Dany, Lionel
Abstract: Purpose: Various studies have shown that the drafting of Advance Directives (ADs) is relatively uncommon. This study was performed to explore cancer patients' attitudes toward ADs, and their reasons for completing or not completing advance directive forms. Methods: The research included interdependent steps designed to gradually collect patients' agreement and comments concerning their participation in an AD study. A thematic content analysis was performed on patients' comments. A total of 147 patients spontaneously agreed to participate before the presentation of the specific theme (AD) of the study. Results: A large majority of the sample reported having no knowledge about ADs. Of the patients who initially agreed to participate, two-thirds declined after the presentation of the theme of the study. The reasons of patients who declined to participate related to avoidance of the issue of death, a focus on present time perspective, or an ambivalence between the AD proposal and recovery plans. Conclusions: This study provides further evidence of the difficulties for patients to express their willingness to engage in AD discussions or research. The extent of the psychological issues experienced by patients and the level of avoidance they expressed raise many questions about the ethical issues and the spread of ADs used in oncology settings.